Evolutionary and biogeographical implications of variation in skull morphology of raccoon dogs (Nyctereutes procyonoides, Mammalia: Carnivora). (20th August 2015) - Kim, Sang‐In; Oshida, Tatsuo; Lee, Hang; Min, Mi‐Sook; Kimura, Junpei
<x xml:space="preserve">Abstract</x> Morphological characteristics reflect geographical variation resulting from adaptation to varying environmental conditions. Carnivore species distributed over a wide geographical range generally have highly polymorphic morphological variation. The raccoon dog (Nyctereutes procyonoides) has a longitudinal distribution restricted to East Asia and the northern Indochina Peninsula. Its unique geographical range makes it an appropriate model to examine how morphological differences are influenced by geography. To demonstrate morphological evolution of Russian, Chinese, Korean and Japanese raccoon dogs predicted by geographical differences, we tested the island rule and Bergmann's rule. We compared craniodental variation among populations and examined morphological implications for intraspecific taxonomic status. Insular raccoon dogs possessed substantially smaller body size than those from the mainland. Moreover, different island effects among Japanese islands were demonstrated by markedly larger occipital condyle breath in the Hokkaido population. Larger skull size in Russian and Hokkaido raccoon dogs could be explained by Bergmann's rule. Based on previous chromosomal and molecular studies and results of our morphological analyses, we suggest Japanese raccoon dogs are a distinct species from the mainland N. procyonoides.